Private Law and Human Rights: New realities - Tkalych, Maxym; Safonchyk, Oksana; Tolmachevska, Yuliia (DIXI, 2020)
Point of view: One of the basic concepts that underlies law as a phenomenon, as well as private law as one of the two areas of law, is the concept of natural law. This concept presupposes that rights and freedoms are an inalienable good of every person, regardless of the will of any external institutions. The ideas of natural law have been expressed in the concept of private law (the fundamental principles of private law are such principles as justice, good faith, reasonableness, dispositiveness, legal certainty, inadmissibility of interference in private affairs, inviolability of property rights, and freedom of contract). Object: The subject of the study is the problems of reforming of private law in modern conditions. The object of research is the social relations that arise in the plane of «person-person» and «state-person» in modern transformation processes. Methodology: The research methodology is formed by methods of analysis, synthesis, and modeling. Additionally, logical-legal, comparative-legal forecasting methods are used. The authors of the article tried to draw a parallel between the concepts of natural law, Roman law and private law. Results and discussion: An analysis of these concepts revealed that each of them is an integral part of the concept of modern Western civilization. At the same time, in modern conditions of pandemic, deglobalization, regionalization, collapse of human rights and the very concept of Western civilization, which is based on the ideas of humanism, liberalism, absolute human rights, inviolability of property rights and respect for privacy, are under threat.